Electioneering in Lithuania - Aleknonis, Gintaras (Political Preferences, 2017)
This article serves as an introductory note to the “Lithuanian chapter” of the journal. A brief description of the electoral history after the restoration of Lithuanian independence in 1990 is provided, the most important political parties are introduced and their interactions shortly explained. The article also describes basic research on electoral topics in Lithuania. Key words: Elections, campaigning, Lithuania